Factors affecting on land alienation procedure at Pejabat Tanah Besut - Azrul Affandy Jusoh
Owning a state land through the local land application process has never been an easy task. Variables such as bureaucracy, red tape, the length of the application process have become public talking points. Therefore, the study entitled 'Factors Influencing the Land Ownership Procedures at the Pejabat Tanah Besut aims to achieve the objectives of identifying the causes of arrears of land applications, and the proposal to reduce the arrears of land application settlement applied in the case study area. The method used to achieve the objective is to use interview and observation methods. As a result of this study the causes of arrears of land applications can be identified such as heavy workload incompatible with increasing numbers of staff, inexperienced staff in legal and computer systems, non-conducive work space, obsolete and frequently damaged computer equipment and land applications too much. The authors have come up with several suggestions for improving the land ownership process such as a fully online land application system such as e-tanah, adding specialized staff and equipment and the creation of a computer master file system.